College physics a strategic approach - Knight, Randall D (Pearson Education Inc, 2015)
This popular workbook helps to bridge the gap from the textbook to homework problems. It provides with short, quick exercises that focus on developing conceptual understanding, key skills, and good problem-solving habits (such as setting up a problem before you try to solve it).